Early childhood caries prevalence and oral hygiene behavior of children under 2 y.o (9 months observation) - Dharli SYAFRİZA (Dentistry Faculty, 2020)
Various factors were believed to play an important role and were closely related to the risk of Early Childhood Caries (ECC), including daily oral hygiene behavior. Oral hygiene of children under 2 years is very dependent on their parents, especially mothers or caregivers. This study revealed the prevalence of ECC and its related to children's oral hygiene behavior after 9 months of observation. A total of 60 caries-free children (deft= 0) under two y.o were observed for 9 months. Without prior dental education regarding oral health care, all subjects were observed for their oral hygiene behavior. The questionnaires were given at the beginning and at the end of the observation and recording the final deft score. After 9 months later, from 60 caries-free children, 19 (31.6%) study subjects were exposed to ECC with a deft average score of 2+2. Oral hygiene behavior related to ECC prevalence in this study (p0.05). In conclusion, the prevalence of ECC was related to poor oral hygiene behavior